The Influence of Content Marketing, Shopping Lifestyle, and User Experience on Purchase Decisions on the Shopee Marketplace - Evi Adriani; Azizah Azizah; Yulina Eliza (International Journal of Islamic Business and Management Review, 2025)
This study aims to analyze the influence of content marketing and shopping lifestyle on the purchasing decisions of Shopee users. The research method used is quantitative, employing a survey approach involving 100 active Shopee users as respondents. Data analysis techniques include multiple linear regression to examine the influence of independent variables on the dependent variable.Research results show that, partially, content marketing, shopping lifestyle, and user experience have a significant influence on purchase decisions on the Shopee marketplace—and so do these factors simultaneously. The implications of this research can serve as a reference for e-commerce businesses in designing more effective marketing strategies that align with the characteristics of today’s digital consumers. Suggestions for Shopee: Increase the amount of relevant and engaging content, such as product tutorial videos, live streaming, and influencer reviews to boost consumer interest. Improve the user interface of both the app and website to make them more intuitive, faster, and user-friendly, and ensure that the payment and delivery systems run smoothly. Customize features and promotions according to consumer trends, such as flash sales, shopping gamification, and wishlist features that support both impulsive and routine shopping behaviors.